Exploring How Financial Literacy and Peer Influence Impact Financial Behavior: Understanding the Role of Locus of Control in Higher Education - Putri Safina Riecka Azzahra; Han Tantri Hardini (The Indonesian Accounting Review, 2026)
This study examines whether the locus of control serves as a mediator in the relationship between peer interaction and financial literacy in students’ financial behavior at Surabaya State University's Faculty of Economics and Business. This study responds to inconsistent prior evidence regarding the mediating role of the locus of control in the financial behavior of university students in developing countries such as Indonesia. Using an explanatory quantitative approach, data were collected from 177 students. Multiple-choice exams were used to gather financial literacy data, and Likert scale questionnaires were used to gather information on peer interaction, locus of control, and financial behavior. Data were analyzed using regression-based path analysis, and Sobel tests were performed using SPSS. The results demonstrate that financial literacy, peer interaction, and locus of control positively and significantly affect financial behavior. Financial literacy and peer interaction also positively affected locus of control. In addition, the locus of control mediates the relationship between financial literacy and financial behavior, and between peer interaction and financial behavior. These findings show that students’ financial behavior is shaped by cognitive, social, and psychological factors simultaneously and clarify the mediating role of the locus of control in the context of higher education in Indonesia.